As estratégias utilizadas para mobilizar a participação do público no programa televisivo Bem Estar da Rede Globo - Delai, Grayce Claudia (2016)
The Science Journalism Health needs to be comprehensive and provide the necessary information for an individual to learn how to achieve full welfare state: physical, psychological and social. Scientific news needs to be didactic, simplified and understandable to all audiences. The health agendas on television, needs to be educational and attractive enough to keep the viewers attentive to the the information disseminated. To understand the strategies used by TV show Bem Estar of the Rede Globo to motivate the public was performed a Content Analysis according to the method of Laurence Bardin. It were analyzed 23 editions of the TV show and 619 interactive posts from the public relating to these editions. In order to understand the personal motivations of viewers, a questionnaire was applied to 13 viewers that interacted with the TV show Bem Estar between August 5 and September 4, 2015, and had been connected to interaction channel of the program by your profile in Facebook social network. In the seeking of elements present in the content of the Program Bem Estar that would have motivated the viewer to attend and participate, it was found that the interaction depends on the second screen to be performed. It has been found that the TV show aims to guide the public about how to stay healthy, and that the themes addressed represent the main motive for mobilizing the audience.